If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -8 = 3m Reorder the terms: -8 + 4m = 3m Solving -8 + 4m = 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -8 + 4m + -3m = 3m + -3m Combine like terms: 4m + -3m = 1m -8 + 1m = 3m + -3m Combine like terms: 3m + -3m = 0 -8 + 1m = 0 Add '8' to each side of the equation. -8 + 8 + 1m = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 1m = 0 + 8 1m = 0 + 8 Combine like terms: 0 + 8 = 8 1m = 8 Divide each side by '1'. m = 8 Simplifying m = 8
| 6+10z=-10+6z | | 4z=6z+8 | | 2j=j+9 | | X^2-6x-96=-130 | | -3f+10=-10+7f | | -3f+10=-10 | | -5b-6=-111 | | 7m=8+6m | | 92+87+88+x=270 | | -22+3=m-5 | | -2n=8+2n | | x^2+42x+360=0 | | 6r-6=3r | | -3v=-4v-10 | | 10+9u=10u | | 12p^2= | | 6z=7z^2 | | 7(5x-2)=84x | | 27x+9=90 | | x+(x+7)=0 | | X+x-5=65 | | (x+5)-(8x-2)=0 | | 17-2y=19 | | -(2/7)y=(3/14)-(5/14) | | 8x=-25+3x | | 4p*2q^2*3p= | | 3p-30/3=2 | | 6h(x^3-4)-(4-x^3)=0 | | 2x-29/4=4 | | 4a=2+a | | 0,4(3-x)-0,7(x+2)=3,1 | | x^3=1/125 |